OVERVIEW OF SUPPORT OBTAINED BY TYPE 2 DIABETES MELLITUS PATIENTS IN SAMPIT, CENTRAL BORNEO: A QUALITATIVE STUDY: DOI: https://doi.org/10.35654/ijnhs.v2i2.126 - Cici Desiyani; Kusnanto Kusnanto; Tri Johan Agus Yuswanto (Alta Dharma Publisher, 2019)
Type 2 diabetes mellitus is a chronic metabolic disease that continues to develop over time and requires complex treatment. while undergoing treatment DM, diabetic patients need supports in order to be able to carry out their treatment on an ongoing basis. This study aims to describe supports obtained by Type 2 DM patients during their treatment and caring. This is a qualitative research study with phenomenological approach. Sampling was conducted from social situation with a sample size 20 participants. Data were collected using semi-structured in-depth interviews and analysis were used Colaizzi methods. The results showed three themes. Theme 1) family supports; 2) social supports, 3) health workers supports. Family supports is the most important part, but the supports from health workers also play a role in increasing the motivation of type 2 DM patients in undergoing treatment and diet. it is important to explore more deeply and more specifically how the role of health workers in the care of DM patients for further studies